2010
DOI: 10.4172/2157-2518.1000108
|View full text |Cite
|
Sign up to set email alerts
|

Oral Submucous Fibrosis: A Clinico-Histopathological Comparative Study in Population of Southern Rajasthan

Abstract: Background: Oral submucous fi brosis (OSMF) is a precancerous condition associated with the use of betel/areca nut in various forms. It is characterized by restricted mouth opening, tongue protrusion and cheek rigidity. Purpose: To correlate the clinical staging with histopathological grading in OSMF patients. Materials and Methods: A hospital-based study was conducted on 100 OSMF cases. A detailed history of each patient was recorded along with clinical examination. Punch biopsy was performed for histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 6 publications
4
24
1
Order By: Relevance
“…The results of the present study are similar to the studies done by Kiran et al (2007), Pandya et al (2009), Goel et al (2010, Rooban et al (2005), Tupkari et al (2007) and Rajendran et al (1994) On contrary, Ceena et al (2009) and Shivakumar et al (2010) on correlating the severity of disease and degree of mouth opening found statistically significant results. The variations in the result can be due to the dependence on various other factors such as site of involvement, extent of fibrosis, involvement of underlying musculature, duration of the disease and difference in the staging system used.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study are similar to the studies done by Kiran et al (2007), Pandya et al (2009), Goel et al (2010, Rooban et al (2005), Tupkari et al (2007) and Rajendran et al (1994) On contrary, Ceena et al (2009) and Shivakumar et al (2010) on correlating the severity of disease and degree of mouth opening found statistically significant results. The variations in the result can be due to the dependence on various other factors such as site of involvement, extent of fibrosis, involvement of underlying musculature, duration of the disease and difference in the staging system used.…”
Section: Discussionsupporting
confidence: 92%
“…On contrary, Goel et al (2010) correlated the habits with mouth opening and histopathological grading and suggested that the daily consumption was more significant than the total duration of the habit and a study done by Modi et al (2012) showed that significant and direct correlation to the manifestation of OSF was seen with frequency rather than duration of chewing.…”
Section: Discussionmentioning
confidence: 93%
“…When the clinical grading was compared with histopathologic grouping there was significant correlation between the two. This was not in accordance with other studies with the exception of one study i.e Shivkumar et al, (2010) study (Goel et al,2010;Debnath et al, 2013;Kumar et al, 2007). Goel et al, (2010) attributed this variation to the possibility of difference in the severity and extent of fibrosis in different regions of the oral mucosa and involved muscles.…”
Section: Discussioncontrasting
confidence: 66%
“…OSMF is predominant among the people of South Asia and is closely associated with the habit of areca nut chewing. Evidence shows that areca nut greatly contributes towards exaggerating the occurrence of OSMF (Goel et al, 2010). The prevalence of OSMF in 2010 was reported to be 6.42% with an estimate of 5 million Indians suffering from this condition (Nigam et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The male preponderance (5.7: 1) seen was similar to many other studies, as generally males are earners in these particular areas and have easy access to consume areca nut and females with social constraints and aesthetic consciousness generally do not consume areca nut or gutkhas. [15][16][17] Most of our cases (30) were in younger individuals (between 25 -29 years). This was similar to Goel et al and Katharia and Maher.…”
Section: Discussionmentioning
confidence: 84%